Effects of the total borehole length and of the heat pump inverter on the performance of a ground-coupled heat pump system. (5th January 2018) - Naldi, Claudia; Zanchini, Enzo
Highlights: An hourly simulation code for multifunction ground-coupled heat pumps is presented. The energy needs of a small residential building in Italy are used as a case study. Unbalanced seasonal loads do not yield a relevant efficiency decrease over 80 years. Increasing the total borehole length can improve the seasonal performance up to 20%. Using an inverter-driven heat pump can improve the seasonal performance up to 40%. Abstract: Ground-Coupled Heat Pumps (GCHPs) are an efficient technology for building heating, cooling and DHW production, which reached a considerable development in the last decade. Accurate simulation tools are becoming important for the optimization of this technology. In this paper, a code for the hourly simulation of GCHP systems is presented, which allows the simulation of multifunction heat pumps for heating, cooling-dehumidifying and DHW production, considers the presence of storage tanks, and applies both to on–off and inverter-driven heat pumps. The energy needs of a residential building in Bologna (Italy) are selected as case study to analyze the effects on the system performance of unbalanced seasonal loads, of the total length of the borehole field and of the heat-pump inverter during a period of 80 years. The obtained results show that the long-term temperature decrease of the ground is small and does not cause relevant decrease of the seasonal COP or increase of the seasonal EER over the years. Increasing the total borehole length can yield an enhancement of the seasonal performance up to 20% for heating, 8% for cooling and 5% for DHW. Using an inverter-driven heat pump instead of an on–off one can improve the system efficiency up to 30% for heating, 40% for cooling and 10% for DHW.